The Jurassic Laberge Group in the Whitehorse Trough of the Canadian Cordillera: Using Detrital Mineral Geochronology and Thermochronology to Investigate Tectonic Evolution - Kellett, Dawn A.; Zagorevski, Alex (Geoscience Canada, 2022)
The Laberge Group is an Early to Middle Jurassic sequence of mostly siliciclastic sedimentary rocks that were deposited in a marginal marine environment in the northern Canadian Cordillera. It forms a long narrow belt with a total thickness of 3–4 km extending for more than 600 km across southern Yukon and northwestern British Columbia. These sedimentary rocks overlap the Yukon-Tanana, Stikinia and Cache Creek terranes that form the main components of the Intermontane superterrane. The Laberge Group contains a record of the erosion of some of these terranes, and also offers some constraints on the timing of their amalgamation and accretion to the Laurentian margin. The Laberge Group was deposited with local unconformity on the Late Triassic Stuhini Group (in British Columbia) and correlative Lewes River Group (in Yukon), both of which are volcanic-rich, and assigned to the Stikinia terrane. The Laberge Group is in turn overlain by Middle Jurassic to Cretaceous clastic rocks, including the Bowser Lake Group in BC and the Tantalus Formation in Yukon. Clast compositions and detrital zircon populations within the Laberge Group and between it and these bounding units indicate major shifts in depositional environment, basin extent and detrital sources from Late Triassic to Late Jurassic. During the Early Jurassic clast compositions in the Laberge Group shifted from sediment- and volcanic-dominated to plutonic-dominated, and detrital zircon populations are dominated by grains that yield ages that approach or overlap their inferred depositional ages. This pattern is consistent with progressive dissection and unroofing of (an) active arc(s) to eventually expose Triassic to Jurassic plutonic suites. Detrital rutile and muscovite data from the Laberge Group indicate rapid cooling and then exhumation of adjoining metamorphic rocks during the Early Jurassic, allowing these to contribute detritus on a more local scale. The most likely source for such metamorphic detritus is within the Yukon-Tanana terrane, and its presence in the Laberge Group may constrain the timing of amalgamation and accretion of the Yukon-Tanana and Stikinia terranes. Thermochronological data also provide new insights into the evolution of the Laberge Group basin. Results from the U–Th/(He) method on detrital apatite suggest that most areas experienced post-depositional heating to 60°C or more, whereas U–Th/(He) results from detrital zircon show that heating to more than 200°C occurred on a more local scale. In detail, Laberge Group cooling and exhumation was at least in part structurally controlled, with more strongly heated areas situated in the footwall of an important regional fault system. The thermochronological data are preliminary, but they suggest potential to eventually constrain the kinematics and timing of inversion across the Laberge Group basin and may also have implications for its energy prospectivity. In summary, the Laberge Group is a complex package of sedimentary rocks developed in an active, evolving tectonic realm, and many questions remain about the details of its sources and evolution. Nevertheless, the available information demonstrates the potential of combined geochronological and thermochronological methods applied to detrital minerals to unravel links between regional tectonics, basin development and clastic sedimentation.